Ewing sarcoma partial regression without GvHD by chondromodulin-I/HLA-A*02:01-specific allorestricted T cell receptor transgenic T cells. (4th May 2017) - Thiel, Uwe; Schober, Sebastian J.; Einspieler, Ingo; Kirschner, Andreas; Thiede, Melanie; Schirmer, David; Gall, Katja; Blaeschke, Franziska; Schmidt, Oxana; Jabar, Susanne; Ranft, Andreas; Alba Rubío, Rebeca; et al.
ABSTRACT: Background : Chondromodulin-I (CHM1) sustains malignancy in Ewing sarcoma (ES). Refractory ES carries a dismal prognosis and patients with bone marrow (BM) metastases do not survive irrespective of therapy. We assessed HLA-A*02:01/CHM1-specific allorestricted T cell receptor (TCR) wild-type and transgenic cytotoxic (CD8 + ) T cells against ES. Patients and Methods : Three refractory HLA-A2 + ES patients were treated with HLA-A*02:01/peptide-specific allorepertoire-derived (i.e., allorestricted) CD8 + T cells. Patient #1 received up to 4.8 × 10 5 /kg body weight HLA-A*02:01 − allorestricted donor-derived wild-type CD8 + T cells. Patient #2 received up to 8.2 × 10 6 /kg HLA-A*02:01 − donor-derived and patient #3 up to 6 × 10 6 /kg autologous allorestricted TCR transgenic CD8 + T cells. All patients were treated with the same TCR complementary determining region 3 allorecognition sequence for CHM1 peptide 319 (CHM1 319 ). Results : HLA-A*02:01/CHM1 319 -specific allorestricted CD8 + T cells showed specific in vitro lysis of all patient-derived ES cell lines. Therapy was well tolerated and did not cause graft versus host disease (GvHD). Patients #1 and #3 showed slow progression, whereas patient #2, while having BM involvement, showed partial metastatic regression associated with T cell homing to involved lesions. CHM1 319 TCR transgenic T cells could be tracked in his BM for weeks. Conclusions : CHM1 319 -TCR transgenic T cells home to affected BM and may cause partial disease regression. HLA-A*02:01/antigen-specific allorestricted T cells proliferate in vivo without causing GvHD.